Protecting Rice Grains in the Post-Genomic Era - Jia, Yulin (IntechOpen, 2019)
This book focuses on recent advances in genetic resources, host - pathogen interactions, assay methods, mechanisms of pathogenesis, and disease resistance. Environmentally benign crop protection methods for major rice diseases such as rice blast, sheath blight, bacterial blight, and newly emerged rice diseases such as false smut and bacterial panicle blight disease are included. The content also contains recent rice breeding methods for higher yield and improved disease resistance, rice processing, delicious rice recipes, and food safety. The book includes a comprehensive understanding of Bacillus thuringiensis toxin and its application for crop protection. Holistically, the book demonstrates successful applications of genomics, physiology, chemistry, genetics, pathology, soil science, and food technology to sustainably protect rice crops for global food safety.